Effect of water availability on volatile‐mediated communication between potato plants in response to insect herbivory. (22nd August 2022) - Vázquez‐González, Carla; Pombo‐Salinas, Laura; Martín‐Cacheda, Lucía; Rasmann, Sergio; Röder, Gregory; Abdala‐Roberts, Luis; Mooney, Kailen A.; Moreira, Xoaquín
Abstract: Airborne plant communication is a widespread phenomenon in which volatile organic compounds (VOCs) from damaged plants boost herbivore resistance in neighbouring, undamaged plants. Although this form of plant signalling has been reported in more than 30 plant species, there is still a considerable knowledge gap on how abiotic factors (e.g. water availability) alter its outcomes. We performed a greenhouse experiment to test for communication between potato plants Solanum tuberosum in response to herbivory by the generalist insect Spodoptera exigua and whether communication was affected by water availability. We paired emitter and receiver potato plants, with half of the emitters damaged by S. exigua larvae and half serving as undamaged controls. Both emitter and receiver plants were factorially subjected to one of two watering treatments: high (i.e. well‐watered) vs. low (i.e. reduced watering) availability, thus effectively teasing apart water availability effects on the emission and reception components of signalling. After 4 days of herbivore feeding, we collected emitter VOCs and receivers were subjected to feeding by S. exigua to test for effects of signalling on induced resistance. Herbivory by S. exigua led to increased VOCs emissions as well as changes in VOCs composition in emitter plants. Furthermore, emitters subjected to low water availability exhibited a weaker induction of VOCs in response to herbivory relative to well‐watered emitters. Results from the feeding bioassay indicated that receivers exposed to VOCs from herbivore‐induced emitters showed lower S. exigua damage (i.e. induced resistance) compared to receivers exposed to undamaged emitters. However, we did not observe a significant effect of water availability in either emitters or receivers on plant signalling effects on receiver resistance. Overall, our study contributes to understanding how the abiotic context affects plant communication by providing evidence of water availability effects on the induction of VOCs that act as airborne signals between plants. The observed changes in induced VOCs due to the water treatment had no detectable consequences for plant communication. Accordingly, the induction of key compounds mediating communication was apparently not compromised by our experimental conditions. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.